Cancer and the microbiome: potential applications as new tumor biomarker. Issue 3 (March 2015) - Shahanavaj, Khan; Gil-Bazo, Ignacio; Castiglia, Marta; Bronte, Giuseppe; Passiglia, Francesco; Carreca, Anna P; del Pozo, José Luis; Russo, Antonio; Peeters, Marc; Rolfo, Christian
<x xml:space="preserve">Abstract</x> Microbial communities that colonize in humans are collectively described as microbiome. According to conservative estimates, about 15% of all types of neoplasms are related to different infective agents. However, current knowledge is not sufficient to explain how the microbiome contributes to the growth and development of cancers. Large and thorough studies involving colonized, diverse and complex microbiome entities are required to identify microbiome as a potential cancer marker and to understand how the immune system is involved in response to pathogens. This article reviews the existing evidence supporting the enigmatic association of transformed microbiome with the development of cancer through the immunological modification. Ascertaining the connection between microbiome and immunological responses with risk of cancer may direct to explaining significant advances in the etiology of cancer, potentially disclosing a novel paradigm of research for the management and prevention of cancer.